Constructicography: Constructicon development across languages - Kyoko Ohara (Constructional Approaches to Language, 2018)
In constructionist theory, a constructicon is an inventory of constructions making up the full set of linguistic units in a language. In applied practice, it is a set of construction descriptions - a "dictionary of constructions". The development of constructicons in the latter sense typically means combining principles of both construction grammar and lexicography, and is probably best characterized as a blend between the two traditions. We call this blend constructicography. The present volume is a comprehensive introduction to the emerging field of constructicography. After a general introduction follow six chapters presenting constructicon projects for English, German, Japanese, Brazilian Portuguese, Russian, and Swedish, respectively, often in relation to a framenet of the language. In addition, there is a chapter addressing the interplay between linguistics and language technology in constructicon development, and a final chapter exploring the prospects for interlingual constructicography. This is the first major publication devoted to constructicon development and it should be particularly relevant for those interested in construction grammar, frame semantics, lexicography, the relation between grammar and lexicon, or linguistically informed language technology.